Tingkat Pelayanan Ruang Terbuka Hijau Publik Berdasarkan Kebutuhan Masyarakat di Perumnas Pucang Gading Demak - Rafi Faishal Azzam; Retno Susanti (Jurusan Perencanaan Wilayah dan Kota, 2022)
Green open space in residential areas is one of the facilities that must be provided as a space for community activities and has an ecological function for the environment. Perumnas Pucang Gading is a settlement that has existed since the 1990s and there is green open space in each hamlet as a space for residents' activities. However, in its utilization, green open space is not widely used and instead is used for personal interests, one of which is for parking lots. This study aims to evaluate the level of green open space services at Perumnas Pucang Gading based on the needs of the community. The research approach was carried out in a quantitative descriptive manner using spatial analysis techniques, scoring, and frequency distribution. The results of the study show that in terms of quantity, the availability of green space services has been 75% fulfilled, namely based on the distribution, range, and area needed. Then in terms of quality, green open space obtained a sufficient/average score from the functional, technical, and behavioral aspects with a score of 3.1 out of 5.0. However, it turns out that the availability of green open space is not in accordance with the criteria needed by the community, namely a sports field with social space and is fulfilled by vegetation elements which are not in accordance with the current existing conditions.